Lots & lots of fire trucks. [videorecording (DVD)] Vol. 2. (Marshall Pub., 2007)
"Here they come ... racing to the rescue, the biggest, bravest, firefighting machines in the world! No matter what your age, if you love fire trucks, we guarantee you'll love this new action-packed DVD!"--Container.